Integrated Simulation Model for Composition and Properties of Gases in Hydrogen Fueled Engine - Mohammed, Kamil; M. M., Rahman; R. A., Bakar (Universiti Malaysia Pahang, 2013)
The composition and thermodynamic properties of combustion products are essential for evaluating the performance of internal combustion engines. This paper presents a simulation model named „HydEnPro‟, to predict the composition and thermodynamic properties of the multi-component gases in hydrogen fueled engine. HydEnPro was developed a set of codes for predicting the chemical equilibrium composition with two databases (NASA and Chemkin) that contain the thermodynamic information about the molecules. The developed codes accessed the thermodynamic databases and equilibrium codes predicted the properties of the multi-component gases. The predictions of HydEnPro were validated against the well-recognized Chemkin Tables, the standard literature and other general simulation models. It shown HydEnPro translation for the databases and its interfaces are correctly implemented. In addition, the accuracy of HydEnPro was emphasized. Hence,HydEnPro can be used in a predictive manner.